The Performance of Fine Resolution Neutron Powder Diffractometer at PTBIN-BATAN - A. Fajar; H. Mugirahardjo (Atom Indonesia, 2010)
We describe the performance of a fine resolution neutron powder diffractometer, DN3, which has been installed at the neutron guide (NG2) in the Neutron Guide Hall about 71 m away from the Multipurpose G. A. Siwabessy reactor core. DN3 has a multi-detector system which consists of 32 3He neutron detectors and soller-type collimation. The resolution curve of the instrument was found to have little variation over a wide angular region. The best resolution is Δ2θ (FWHM) of 0.23º and Δd / d of 5x10-3, where 2θ and d are scattering angle and d-spacing, respectively. The instrument provides sample environment of low temperatures using a cryostat having a temperature range of 10-300K. Several experimental results, interlaboratory comparison study and he next activities to improve the performance of DN3 equipment have also been discussed. Received: 15 October 2009; Revised: 12 April 2010; Accepted: 21 April 2010